Parenting sense of competence among chinese parents of premature infants: a cross-sectional study - Long Huang; Xiao-juan Wang; Gui-hua Liu; Xiao-ting Li; Yu-hong Zhang; Bing-yue Zhao; Rong-fang Hu (BMC, 2023)
Abstract Background Parenting sense of competence is not only indispensable to the wellbeing of the parents of premature infants, but is also pivotal to the overall development of these infants. This study examined the level of parenting sense of competence and its associated factors in Chinese parents of preterm infants. Methods This cross-sectional study was performed at a university teaching hospital in Fuzhou (China) from December 2021 to April 2022. Data were collected using the Parenting Sense of Competence Scale, Edinburgh Postnatal Depression Scale, Social Support Rating Scale, Parenting Care Knowledge Subscale, Parenting Care Skill Subscale, and a sociodemographic questionnaire. Results A total of 401 Chinese parents were included in the analysis. The average parenting sense of competence scale score was 70.93 ± 13.06. After controlling for demographic characteristics, parenting knowledge (β = 0.149, P = 0.013), parenting skills (β = 0.241, P < 0.001), social support (β = 0.184, P < 0.001) and depression (β = −0.272, P < 0.001), were significantly associated with the parenting sense of competence score, and explained 43.60% of the variance in this score. Conclusions Chinese parents of preterm infants were found to have a moderate parenting sense of competence. This could be further improved through efforts aimed at reducing depressive symptoms and increasing parenting knowledge, parenting skills, and social support.